Similarity analysis of protein binding sites: A generalization of the maximum common subgraph measure based on quasi-clique detection - Boukhris, I.; Elouedi, Z.; Fober, T.; Mernberger, M.; Hüllermeier, Eyke (In Proceedings IDA-2009, 9th International Symposium on Intelligent Data Analysis, Pisa / Italy)

Fuzzy modeling of labeled point cloud superposition for the comparison of protein binding sites - Fober, T.; Hüllermeier, Eyke (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

A fuzzy variant of the Rand index for comparing clustering structures - Hüllermeier, Eyke; Rifqi, M. (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

Methoden und Werkzeuge für einen effizienten Ultraschallsensorentwurf - Henning, Bernd

Trends in ultrasonic transducer design - Henning, Bernd
Ultrasonic sensors are widespread in the process industry for example to measure flow, filling level, density or substance concentration in liquid mixtures today. On one side technically high demands are made to the ultrasonic sensors on the other side the production of the ultrasonic sensors has to be more and more cost-efficient. Today, these two contrary demands only can be met by the use of efficient development tools. This contribution describes the state of technology in the field of the computer-assisted ultrasonic transducer development, however, also shows the limits.

Ultrasonic Sensors for Process Applications - Sensor Design - Henning, Bernd; Rautenberg, Jens; Schröder, Andreas; Unverzagt, Carsten (Proceedings Sensor 2009)
Today, ultrasonic sensor systems are often applied in process technology. For the opening up of new industrial fields of application, such as the non-invasive process tomography, ultrasound sensors are necessary which are stable and adapted optimally under process conditions. Only with such optimized ultrasonic sensors the functionality of the sensor systems can be enlarged decisively with support of a complex measurement data evaluation. This contribution deals especially with the design process.

Computer assisted design of transducers for ultrasonic sensor systems - Henning, Bernd; Rautenberg, Jens; Unverzagt, Carsten; Schröder, Andreas; Olfert, Sergei (Journal of Measurement Science and Technology, MST)
In this contribution, possibilities and methods for computer-assisted design of ultrasound transducers are described. These transducers are essential for an ultrasonic sensor design, e.g. for continuous non-invasive determination of quantities that are important in process technology. To achieve technical reliability and robustness, the precise determination of all acoustic properties of the used sensor materials is of great importance. Problem-oriented modeling, numerical simulation, special optimization algorithms and improved methods for the visualization of propagating waves offer new and promising possibilities for developing ultrasonic transducers with enhanced properties.

Generating of short ultrasonic pulses using active damping - Rautenberg, Jens; Olfert, Sergei; Henning, Bernd
In non-destructive testing (NDT) with ultrasound the emission of short pulses is essentially if the echoes of nearby obstacles should be separated from the emitted signal. In this contribution a new approach is shown how to gene-rate a short ultrasonic pulse using a 3$-$1 composite transdu-cer. Therefore the ceramic bars, which are embedded in a polymer matrix, will be regarded as an exciter for the entire structure. After the pulse excitation the same bars can also be used for active damping to increase the bandwidth of the entire system. The Mason model serves as a basis for the de-scription of the ultrasonic transducer and is extended to the composite structure. The excitation signal is adaptively mo-dified by a suitable signal processing. Therefore the changes of boundary conditions, like the ambient temperature or acoustic impedance of adjacent media are considered.

Interdisciplinary Collaboration in a Visualization Course - Domik, Gitta (Informatics Education Europe IV, November)

Einsatz von Simulationswerkzeugen in der Entwicklungskette von ultrahochfesten warmgeformten Strukturkomponenten im Fahrzeugleichtbau* - Böke, Johannes; Erhardt, Rüdiger; Rostek, Wilfried; Tröster, Thomas (Materials Testing)

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, B.; Elser, D.; Bartley, Tim; Sabuncu, M.; Wittmann, C.; Sych, D.; Marquardt, C.; Leuchs, G. (Applied Physics B)

Merging chemical and biological space: Structural mapping of enzyme binding pocket space - Weskamp, N.; Hüllermeier, Eyke; Klebe, G. (Proteins)

FURIA: An Algorithm for unordered fuzzy rule induction - Hühn, J.; Hüllermeier, Eyke (Data Mining and Knowledge Discovery)

Why fuzzy decision trees are good rankers - Hüllermeier, Eyke; Vanderlooy, S. (IEEE Transactions on Fuzzy Systems)

Combining instance-based learning and logistic regression for multilabel classification - Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Fuzzy operator trees for modeling rating functions - Yi, Y.; Fober, T.; Hüllermeier, Eyke (International Journal of Computational Intelligence and Applications)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (Bioinformatics)

FR3: A fuzzy rule learner for inducing reliable classifiers - Hühn, J.; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Supporting case-based retrieval by similarity skylines: Basic concepts and extensions - Hüllermeier, Eyke; Vladimirskiy, I.; Prados Suarez, B.; Stauch, E. (Künstliche Intelligenz)

Optimal algorithms for page migration in dynamic networks - Bienkowski, Marcin; Byrka, Jaroslaw; Korzeniowski, Miroslaw; Meyer auf der Heide, Friedhelm (Journal of Discrete Algorithms)

An apparatus for the determination of speeds of sound in fluids - Gedanitz, Holger; Dávila, María J.; Baumhögger, Elmar; Span, Roland (The Journal of Chemical Thermodynamics)

Social Search: Exploring and Searching Social Architectures in Digital Networks - Trier, Matthias; Bobrik, Annette (IEEE Internet Computing)

Enabling social media content quality assurance using social network analysis - Sanmateu, Maria-Amparo; Trier, Matthias; Lienicke, Andreas; Rederer, Andreas (9th International Conference On Innovative Internet Community Systems I2CS 2010)

Content-based Community Detection in Social Corpora - Bobrik, Annette; Trier, Matthias (Proceedings Wirtschaftsinformatik)

Odp2cp – ein rapid E-Learning Ansatz zur einfachen Produktion Scorm-konformer Lerninhalte - Trier, Matthias; Herzog, Michael; Möller, Daniel (Proceedings Wirtschaftsinformatik)

Cooperation and coding framework - Biermann, Thorsten; Polgar, Zsolt Alfred; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Combining for cooperative WLANs-a reality check based on prototype measurements - Valentin, Stefan; Woldegebreal, Dereje H; Volkhausen, Tobias; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Improving network coded cooperation by soft information - Volkhausen, Tobias; Woldegebreal, Dereje H; Karl, Holger (Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009. SECON Workshops' 09. 6th Annual IEEE Communications Society Conference on)

On the usefulness of fuzzy sets in data mining - Hüllermeier, Eyke (Views on Fuzzy Sets and Systems from Different Perspectives: Philosophy and Logic, Criticisms and Applications)

Statistics-based ID management for load balancing in structured P2P networks - Warneke, Daniel; Dannewitz, Christian (2009 IEEE 34th Conference on Local Computer Networks)

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))

Vacancy clusters created via room temperature irradiation in 6H-SiC - Scholle, A.; Greulich-Weber, S.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physica B: Condensed Matter)

Decision tree and instance-based learning for label ranking - Cheng, W.; Hühn, J.; Hüllermeier, Eyke (in Proceedings ICML-2009, 26th International Conference on Machine Learning, Montreal, Canada)

Binary decomposition methods for multipartite ranking - Fürnkranz, J.; Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings ECML/PKDD-2009, European Conference on Machine Learning and Principles and Knowledge Discovery in Databases, Bled Sloveniaery in Databases, Bled, Slovenia)

A new instance-based label ranking approach using the Mallows model. In Advances in Neural Networks - Cheng, W.; Hüllermeier, Eyke (in Proceedings 6th International Symposium on Neural Networks, Wuhan, China)

A Multithreaded Framework for Sequential Monte Carlo Methods on CPU/FPGA Platforms - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Towards Models for Many-Cores: The Case for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the Workshop on Many-Cores, International Conference on Architecture of Computing Systems (ARCS))

ARMLang: A Language and Compiler for Programming Reconfigurable Mesh Many-Cores - Giefers, Heiner; Platzner, Marco (Reconfigurable Architectures Workshop (RAW), Proceedings of the International Parallel and Distributed Processing Symposium)

Cooperative Multithreading in Dynamically Reconfigurable Systems - Lübbers, Enno; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

Program-driven Fine-grained Power Management for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

An adaptive Sequential Monte Carlo framework with runtime HW/SW repartitioning - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the 2009 International Conference on Field-Programmable Technology (FPT))

Proof-carrying Hardware: Towards Runtime Verification of Reconfigurable Modules - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Rare-earth defect pairs in GaN: LDA+U calculations - Sanna, Simone; Schmidt, Wolf Gero; Frauenheim, Th.; Gerstmann, Uwe (Physical Review B)

Adsorption structure of cyclopentene on InP(001)(2×4) - Passmann, Regina; Favero, Priscila; Schmidt, Wolf Gero; Miotto, Ronei; Braun, Walter; Richter, Wolfgang; Kneissl, Michael; Esser, Norbert; Vogt, Patrick (Physical Review B)

Role of Dihydrogen Bonds for the Stabilization of Self-Assembled Molecular Nanostructures - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)